2008
DOI: 10.1007/s11104-008-9737-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving NaCl resistance of red-osier dogwood: role of CaCl2 and CaSO4

Abstract: The influence of Ca 2+ salts on the resistance of red-osier dogwood (Cornus sericea) seedlings to salinity was investigated. Red-osier dogwood seedlings were exposed to 5 and 10 mM of CaCl 2 or CaSO 4 in the presence or absence of 50 mM NaCl for 40 days in a controlled environment. Seedlings exposed to CaCl 2 and CaSO 4 recovered from NaClinduced transpiration reduction after 20 days at a concentration of 10 mM and after 30 days at a concentration of 5 mM; while in absence of additional Ca 2+ , the seedlings r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Some authors suggested that Ca can help to mitigate also the osmotic effect of salinity through the accumulation of organic solutes such as proline and glycinebetaine (Girija et al, 2002). Proline is a compatible solute involved in osmotic adjustment and acts as a non-toxic osmotic solute stabilizing the structure of macromolecules and organelles in plants subjected to salt stress (Munns and Tester, 2008;Renault and Affifi, 2009). CaCl 2 was found to mitigate the NaCl-induced stress through the enhancement of proline accumulation in many plant species [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that Ca can help to mitigate also the osmotic effect of salinity through the accumulation of organic solutes such as proline and glycinebetaine (Girija et al, 2002). Proline is a compatible solute involved in osmotic adjustment and acts as a non-toxic osmotic solute stabilizing the structure of macromolecules and organelles in plants subjected to salt stress (Munns and Tester, 2008;Renault and Affifi, 2009). CaCl 2 was found to mitigate the NaCl-induced stress through the enhancement of proline accumulation in many plant species [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the addition of 10 mM Ca 2? together with NaCl treatment reduces the accumulation of proline in leaf tissues of red-osier dogwood (Renault and Affifi 2009). These studies provide the evidence that exogenous Ca supplement can regulate proline levels in high plants exposed to salinity stress, whereas the conclusions are different, and even contradictory.…”
Section: Because Increased Gk and Decreased Oat Activitiesmentioning
confidence: 79%
“…Although alleviation of Na + toxicity by supplemental Ca 2+ was confirmed, the responses varied with different plant species. Under similar saline-sodic conditions, amendments of Ca 2+ were found to obviously increase K + /Na + selectivity of both roots and shoots (SA and ST values) in Medicago sativa (Al-Khateeb, 2006) and Cornus sericea (Renault & Affifi, 2009). This is in contrast with Wang, Zhang & Flower (2007), who reported that amendments of Ca 2+ had no influence on SA and ST values of Suaeda maritima.…”
Section: Effects Of Ca 2+ On Sa and St Valuesmentioning
confidence: 84%